2020
DOI: 10.3389/fgene.2020.00391
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Early Prediction Model for Subarachnoid Hemorrhage With Genetic and Signaling Pathway Analysis

Abstract: Subarachnoid hemorrhage (SAH) is devastating disease with high mortality, high disability rate, and poor clinical prognosis. It has drawn great attentions in both basic and clinical medicine. Therefore, it is necessary to explore the therapeutic drugs and effective targets for early prediction of SAH. Firstly, we demonstrate that LCN2 can effectively intervene or treat SAH from the perspective of cell signaling pathway. Next, three potential genes that we explored have been validated by manually reviewed exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…where k represents the lag order and is the error term. We use the F-test [23,[31][32][33][34][35][36][37][38][39] to verify the null hypothesis (Eq. ( 6)).…”
Section: Spatiotemporal Correlation Analysis Of the Anthraxmentioning
confidence: 99%
“…where k represents the lag order and is the error term. We use the F-test [23,[31][32][33][34][35][36][37][38][39] to verify the null hypothesis (Eq. ( 6)).…”
Section: Spatiotemporal Correlation Analysis Of the Anthraxmentioning
confidence: 99%
“…In summary, our study not only identified the brain regions affected by secondary neurological dysfunction after IVH stimulation from a 3D perspective but also allows for the further investigation of driving cell types and molecular pathways, which might benefit the construction of translational intervention strategies for secondary brain injuries after IVH at the molecular and cellular levels in the distant future ( 20 22 ). Finally, our study is available via a web service ( ).…”
Section: Introductionmentioning
confidence: 96%
“…In summary, our study not only identified the brain regions affected by secondary neurological dysfunction after IVH 1517 from a 3D perspective but it also has the potential for us to construct corresponding intervention strategies for acute traumatic brain trauma at the molecular and cellular levels in the distant future.…”
Section: Introductionmentioning
confidence: 96%